A locus on barley chromosome 5H affects adult plant resistance to powdery mildew - Gupta, Sanjiv (Mol Breed, 2018)
Adult plant resistance against plant pathogens is of interest as a means to achieve durable resistance. Prior to this research, the barley lines CLE210 (from Uruguay) and Denar (from the Czech Republic) had been reported to exhibit adult-plant resistance against powdery mildew. Here, populations of doubled haploid lines from crosses of these lines with the susceptible cultivar Baudin were evaluated for powdery mildew resistance in field experiments. Using linkage maps constructed from genotyping-by-sequencing (GBS) data, it was determined that differences in resistance were largely attributable to a region on the long arm of chromosome 5H (5HL). Therefore, KASP(™) assays were developed based on GBS tag sequences mapped on that chromosome, providing more reliable genetic maps. In each population, a large-effect QTL was mapped on 5HL. As no sequence variation was detected between CLE210 and Denar in this region of 5HL, the two sources of resistance may be identical by descent in the QTL region and carry the same resistance gene. Marker assays from the QTL region were evaluated on a panel of barley lines, providing information that breeders could use to select assays for use in marker-assisted selection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11032-018-0858-2) contains supplementary material, which is available to authorized users.